Tourism Facilities on Balinese Traditional Housing Extensions in Ubud Village Bali (in Term of Environmental Sustainability) - Putra, I Dewa Gede Agung Diasana (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2012)
Tourism is one of the biggest income generators especially for developing countries. Regarding tourism facilities, most people at tourism areas extend their houses as a home stay, a restaurant, an art shop, salons, and other facilities. Without properly manage, that will have severe impacts upon local communities and environment.The housing extensions phenomena as tourism facilities and sustainable issue in tourism areas occur at some rural areas in the world including Indonesia and Bali, especially Ubud Village. These house extensions are often designed with adoption of tourism standard, for example, the people tend to adopt the new technology such as using air conditional to anticipate the increase of local temperature (as the effect of climate change). In order to overcome the ecological problem and energy, they use modern building material such as aluminum, plastic, asbestos, etc. That building are often designed by less taking local characteristic of tropical environment. Consequently, the cost was excessively high and the impact on the environment was negative.The objective of this study is to know how application of Balinese architecture in tourism facilities at Ubud Village. In order to achieve this objective, this research uses stratified random sample survey strategy, and case studies.The result of research shows that generally the tourism facilities at Ubud Village has been far away use Balinese architecture principle like ventilation, material, ornament landscape etc. On the other hand, many facilities use air conditioning and other equipments to find comfortable in the room. That is wasteful of energy and unfriendly to environment. The solutions suggested in this research are the use of sun shading to control of sunlight both vertical and horizontal shading to decrease use of air conditional; the arrangement of the buildings, the attention on environment , the use of material etc.Keywords: extension housing, energy, sustainable